(untitled) (UNED Research Journal, 2020)
Introduction: The production of textbooks in the Costa Rican Distance University must use a series of elements needed for distance education. Objective: To identify the most important educational elements used by the editors. Methods: We used a questionnaire and an editor’s focus group to identify the frequency for each element in 24 textbooks. Results: More than 90% of the didactic units contain: graphs or diagrams, charts, definitions, practical cases, didactic discourse, “attractions”, examples and signs. Between 70 and 90% use: images, attention calls, logical sequence and inserted questions. Less than 70% use anecdotes, establishment of contrary points, humanization of the text, summaries, timelines and metaphors. Conclusions: While most of the recommended elements are used, there is room for improvement in the variety and subject adaptation of learning elements used in these textbooks.